Influence of glycated hemoglobin on thromboinflammation in acute ischemic stroke: a retrospective, propensity score matching study - Wang, Liuding; Chen, Yifan; Liu, Longtao; Jia, Min; Zhang, Yunfan; Chang, Ze; Gong, Zhiyi; Lyu, Jian; Liang, Xiao; Zhang, Yunling (Frontiers in Endocrinology, 2025)
BackgroundHyperglycemia is acknowledged as a pivotal factor associated with poor prognosis in acute ischemic stroke (AIS). The intricate interplay among hyperglycemia, thrombosis, and inflammation has garnered significant attention. Therefore, we aimed to investigate the association between hemoglobin A1c (HbA1c) and risk of thrombosis, and the role of inflammation, in patients with AIS.MethodsA total of 1,291 patients with AIS were identified from Xiyuan Hospital, China Academy of Chinese Medical Sciences. A propensity score matching was used to address baseline imbalances. AIS patients were divided into a high HbA1c group (n = 419) and a control group (n = 656) based on whether their initial HbA1c levels upon admission were above or below 6.5%. Thrombosis was assessed using coagulation parameters. Inflammation was reflected by markers such as the neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), and systemic inflammatory response index (SIRI). Chi-square test, independent sample t-test, Mann-Whitney U test, and logistic regression were used for correlation analysis.ResultsIn AIS patients, HbA1c levels > 6.5% were significantly associated with abnormal coagulation function and elevated inflammatory response. Among AIS patients with elevated HbA1c, high fibrinogen levels were significantly correlated with increased inflammatory markers such as SII and SIRI. Furthermore, HbA1c > 6.5% was identified as an independent predictor for hypercoagulability in AIS patients (OR = 1.74, 95% CI 1.17 − 2.60, P = 0.006).ConclusionsElevated HbA1c levels were associated with severe hypercoagulability and heightened inflammatory responses following AIS onset. Elevated HbA1c levels may contribute to poorer outcomes, likely due to the thromboinflammation.